Analisis Penerapan Permendagri No. 20 Tahun 2018 Tentang Pengelolaan Keuangan Desa (Studi Pada Desa Pangeran Kec.Kabaruan, Kab. Kep.Talaud) - Joshua Duduwong Matei; Florence O. Moroki; Pricilia J. Pesak (Politeknik Raflesia Press, 2026)
This study aims to examine the implementation of Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management in Pangeran Village, Kabaruan District, Talaud Islands Regency. The study focuses on aspects of information transparency, community participation, and accountability in village financial governance. The study used a qualitative descriptive approach to gain a comprehensive understanding of the regulation's implementation process. Data collection was conducted through in-depth interviews, field observations, and document review. Research informants included the village head, village treasurer, village officials, and community members involved, both directly and indirectly, in village financial management activities.The results indicate that administratively, village financial management has been carried out in accordance with the stages stipulated in Minister of Home Affairs Regulation Number 20 of 2018, namely planning, implementation, administration, reporting, and accountability. However, implementation has not been fully optimal. The level of community involvement in the planning and oversight processes remains relatively low. Furthermore, financial reports have not been presented in a format that is simple and easily understood by the general public. Oversight mechanisms have also not been implemented consistently and effectively. Based on these findings, it can be concluded that although regulations have been formally implemented, various improvements are still needed. Increasing the capacity of village officials, improving the quality and clarity of financial reporting, and strengthening inclusive community participation are crucial steps to promote more transparent and accountable village governance.